(untitled) (Baghdad Science Journal, 2022)
In this study we focused on the determination of influence the novel synthesized thiosemicarbazide derivative "2-(2-hydroxy-3-methoxybenzylidene) hydrazinecarbothioamide" (HMHC) influenced the corrosion inhibition of mild steel (MS) in a 1.0 M hydrochloric acid acidic solution.This is in an effort to preserve the metal material by maintaining it from corrosion.The synthesized inhibitor was characterized using elemental analysis, and NMR-spectroscopy. Then the corrosion inhibition capability of (HMHC) was studied on mild steel in an acidic medium by weight loss technique within variables [temperature, inhibitor concentration, and time]. The immersion periods were [1:00, 3:00, 5:00, 10:00, 24:00, and 72:00] hours and the temperature range was (303-333) K. Various concentration of (HMHC) were used and the immersion periods were [0.00, 0.001, 0.05, 0.10, 0.15, 0.20, 0.25, and 0.50] g/L. The prepared derivative has shown the ability to inhibit corrosion. It has been observed that the rate of erosion decreases with the increasing concentration of the prepared inhibitor and increases with the increasing temperature of the solution. The most promising inhibitor action is at 0.5 g/L with an inhibition efficiency of 90.2%. Where it found that the adsorption process of HMHC obeys the Langmuir isotherm model. The electronic properties of the HMHC molecules were obtained from density function theory (DFT) quantum chemical approach. The experimental approach and theoretical results were found to have impressive correlations.